Preclinical evaluation of chimeric antigen receptor T cells targeting the carcinoembryonic antigen as a potential immunotherapy for gallbladder cancer - Ernesto Lopez; Sofía Hidalgo; Eduardo Roa; Javiera Gómez; Carlos Hermansen Truan; Evy Sanders; Cristian Carrasco; Rodrigo Pacheco; Flavio Salazar-Onfray; Manuel Varas-Godoy; Vincenzo Borgna; Alvaro Lladser (OncoImmunology, 2023)
Gallbladder cancer (GBC) is commonly diagnosed at late stages when conventional treatments achieve only modest clinical benefit. Therefore, effective treatments for advanced GBC are needed. In this context, the administration of T cells genetically engineered with chimeric antigen receptors (CAR) has shown remarkable results in hematological cancers and is being extensively studied for solid tumors. Interestingly, GBC tumors express canonical tumor-associated antigens, including the carcinoembryonic antigen (CEA). However, the potential of CEA as a relevant antigen in GBC to be targeted by CAR-T cell-based immunotherapy has not been addressed. Here we show that CEA was expressed in 88% of GBC tumors, with higher levels associated with advanced disease stages. CAR-T cells specifically recognized plate-bound CEA as evidenced by up-regulation of 4-1BB, CD69 and PD−1, and production of effector cytokines IFN-γ and TNF-α. In addition, CD8+ CAR-T cells up-regulated the cytotoxic molecules granzyme B and perforin. Interestingly, CAR-T cell activation occurred even in the presence of PD-L1. Consistent with these results, CAR-T cells efficiently recognized GBC cell lines expressing CEA and PD-L1, but not a CEA-negative cell line. Furthermore, CAR-T cells exhibited in vitro cytotoxicity and reduced in vivo tumor growth of GB-d1 cells. In summary, we demonstrate that CEA represents a relevant antigen for GBC that can be targeted by CAR-T cells at the preclinical level. This study warrants further development of the adoptive transfer of CEA-specific CAR-T cells as a potential immunotherapy for GBC.